Fundamentals of organization and trends of academic professional music education in the Ukraine - Matselyukh, Olena (e-Pedagogium, 2019)
This publication deals with the structure of modern musical schooling, as well as school as a complex of didactic, theoretical and practical aspects of learning. This came to light because of new concepts of musical education, which became the flagship of children's schooling, and the practical achievements in pedagogical endeavours of Ukrainian composer Bohdan Kotyuk: ``Through studying folklore to the formation of students' national consciousness''.
Keywords: didactics; music education; schooling; shops and fraternities; Ukrainian music professionalism; Lviv School; concepts of music education; composer Bohdan Kotyuk.